Large-scale analysis of SARS-CoV-2 envelope protein sequences reveals universally conserved residues - Vivek Darapaneni (Microbes and Infectious Diseases, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the ongoing COVID-19 pandemic that has devastated mankind with an unprecedented impact on both health and economic condition globally. The envelope protein of SARS-CoV-2 is a multifunctional viroporin across endoplasmic reticulum-Golgi intermediate compartment. SARS-CoV-2 envelope (E) protein plays a crucial role in the virus life cycle. The objective of the present study was to identify the residue conservation in the SARS-CoV-2 E protein. The study was based on 2,654,250 amino acid sequences for the E protein. On the whole, this study exposed residues that are universally conserved among different strains of SARS-CoV-2. These universally conserved residues might be involved in either structure stabilizing or protein-protein interactions. The conserved residues identified in the present study in conjunction with structural analysis of the E protein could form the basis for designing universal anti-SARS-CoV-2 drugs which are resistant to mutations arising in the future.